200k views
5 votes
Please help me folks.

Please help me folks.-example-1

1 Answer

5 votes

Answer:

3
x^(5) (x + 2)(3x + 5)

Explanation:

Given

9
x^(7) + 33
x^(6) + 30
x^(5) ← factor out 3
x^(5) from each term

= 3
x^(5) (3x² + 11x + 10) ← factor the quadratic

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term

product = 3 × 10 = 30 and sum = + 11

The factors are 6 and 5

Use these factors to split the x- term

3x² + 6x + 5x + 10 ( factor the first/second and third/fourth terms )

= 3x(x + 2) + 5(x + 2) ← factor out (x + 2) from each term

= (x + 2)(3x + 5), thus

3x² + 11x + 10 = (x + 2)(3x + 5)

and

9
x^(7) + 33
x^(6) + 30
x^(5) = 3
x^(5) (x + 2)(3x + 5)

User Evanwong
by
5.8k points